Difference in the Effectiveness of Dysmenorrhea Exercise and Warm Compress to Relieve Menstrual Pain - Vera Iriani Abdullah; Maryati (EMBRIO: Jurnal Kebidanan, 2022)
Dysmenorrhea is a common complaint experienced before or during a woman’s period. Dysmenorrhea can be treated by applying pharmacological and non-pharmacological methods to relief pain. Pharmacological intervention involves administration of pain medication, while non-pharmacological intervention involves Dysmenorrhea exercise and warm compress. This study aims to determine the difference in the effectiveness of dysmenorrhea exercise and warm compress to relieve menstrual pain. This was a quasi-experimental study with post-test two groups design. 20 samples were selected using purposive sampling technique and assigned into 2 groups. Data were analyzed using the Mann-Whitney statistical test. The results showed that there was no significant difference in effectiveness between Dysmenorrhea exercise and warm compress to relieve menstrual pain, with a p-value of 0.127>0.05. It can be concluded that there was no difference in effectiveness between Dysmenorrhea exercise and warm compress. However, based on the score, it was revealed that warm compress was more effective in relieving menstrual pain than Dysmenorrhea exercise.